Security for mobility / edited by Chris J. Mitchell. - Mitchell, Chris, 1953- (IEE telecommunications series ;, 2004)
Over the last decade, mobile telecommunications has grown dramatically, from a niche technology to a massive industry. This text consists of 17 chapters on various topics of importance to current developments in security for mobility.